2010
DOI: 10.3233/jad-2010-100066
|View full text |Cite
|
Sign up to set email alerts
|

Calretinin Interneurons are Early Targets of Extracellular Amyloid-β Pathology in PS1/AβPP Alzheimer Mice Hippocampus

Abstract: Abstract. Specific neuronal networks are preferentially affected in the early stages of Alzheimer's disease (AD). The distinct subpopulations of hippocampal inhibitory GABAergic system have been shown to display differential vulnerability to neurodegeneration in AD. We have previously reported a substantial loss of SOM/NPY interneurons, whereas those expressing parvalbumin were unaltered, in the hippocampus of 6 month-old PS1/AβPP transgenic mice. In the present study, we now investigated the pathological chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
65
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 45 publications
11
65
0
1
Order By: Relevance
“…This lack of evident changes in GABAergic terminals is in line with the recent report showing that the number of GABAergic neurons is not altered in early phases of AD (Krantic et al, 2012) being only modified at later stages of AD (Hardy et al, 1987b;Bell et al, 2003León-Espinosa et al, 2012). However, this finding should not hinder the evidence that there are early changes in the activity of GABAergic neurons in early AD (Baglietto-Vargas et al, 2010;Verret et al, 2012), typified by a desynchronization of hippocampal circuits (reviewed in Palop and Mucke, 2010) which correction with levetiracetam results in the preservation of memory performance (Sanchez et al, 2012). Since this is proposed to result from the dysfunction of particular populations of interneurons (BagliettoVargas et al, 2010;Verret et al, 2012), it is possible that putative changes in the presynaptic density and function of these particular populations may not be measurable with a global marker of GABAergic terminals such as vGAT.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This lack of evident changes in GABAergic terminals is in line with the recent report showing that the number of GABAergic neurons is not altered in early phases of AD (Krantic et al, 2012) being only modified at later stages of AD (Hardy et al, 1987b;Bell et al, 2003León-Espinosa et al, 2012). However, this finding should not hinder the evidence that there are early changes in the activity of GABAergic neurons in early AD (Baglietto-Vargas et al, 2010;Verret et al, 2012), typified by a desynchronization of hippocampal circuits (reviewed in Palop and Mucke, 2010) which correction with levetiracetam results in the preservation of memory performance (Sanchez et al, 2012). Since this is proposed to result from the dysfunction of particular populations of interneurons (BagliettoVargas et al, 2010;Verret et al, 2012), it is possible that putative changes in the presynaptic density and function of these particular populations may not be measurable with a global marker of GABAergic terminals such as vGAT.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, the cholinergic hypothesis of AD assumes a particular susceptibility of cholinergic neurons (reviewed in Q1 Bartus et al, 1982;Auld et al, 2002), reflecting a primary affection of cholinergic terminals in cortical regions early in AD (Hu et al, 2003). More recently, several studies have suggested a particular vulnerability of glutamatergic synapses Kirvell et al, 2006;Kashani et al, 2008;Minkeviciene et al, 2008;Proctor et al, 2010), whereas other studies have instead reported that it is GABAergic neurons that are initially affected in early AD (Agarwal et al, 2008;Baglietto-Vargas et al, 2010;Verret et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Immunohistochemistry against DCX, a commonly used neuroblast marker that correlates well with the number of newly generated neurons in the hippocampus (Brown et al, 2003), supported these observations. Our data are in line with previously published studies demonstrating altered neurogenesis in AD (Baglietto-Vargas et al, 2010;Moon et al, 2014;Tatebayashi, 2003).…”
Section: Calretinin Immunoreactivitysupporting
confidence: 95%
“…In this sense, the selective inhibitory effect of A␤ oligomers (NGF Ͼ IGF-1 ϭ insulin Ͼ BDNF) might contribute to this decreased signal and, in consequence, be implicated in the preferential vulnerability of the cholinergic system observed in AD. It has also been demonstrated that A␤ oligomers could directly bind to p75NTR (55,58) producing the formation of neuritic dystrophies (also observed in our model) (30,59,60) and the activation of c-Jun kinases mediating cell degeneration (61). Thus, the appearance of A␤ oligomers could actively decrease the trophic support, interacting with trophic receptors (this work), and/or increase the toxic signaling activating death receptors such as p75NTR.…”
Section: Discussionsupporting
confidence: 62%